Inicia la sessió
 Llibres Llibres 41 - 50 de 178 sobre A. {cos a = cos b cos c + sin b sin c cos A. cos b = cos a cos c + sin a sin c cos....
A. {cos a = cos b cos c + sin b sin c cos A. cos b = cos a cos c + sin a sin c cos B. cos c = cos a cos b + sin a sin b cos C.
The elements of plane and spherical trigonometry. [With] Key - Pągina 149
per William Rossiter - 1868
Visualització completa - Sobre aquest llibre

## Surveying and Navigation: With a Preliminary Treatise on Trigonometry and ...

Aaron Schuyler - 1873 - 482 pągines
...group, (1) cos a = cos b cos c -f- sin b sin c cos A. (2) cos b = cos a cos c + sin a sin c cos J3. (3) cos c = cos a cos b + sin a sin b cos C. 137. Proposition III. The co-sine of either angle of a spherical triangle is equal to the product of...
Visualització completa - Sobre aquest llibre

## Plane and Spherical Trigonometry and Mensuration

Aaron Schuyler - 1875 - 184 pągines
...A'—~ cos B' cos C' — sin B' sin C" cos a'. — cos. B'= cos A' cos C"— sin A' sin C' cos b'. — cos C' = cos A' cos B' — sin A' sin B' cos c'. Changing the signs and omitting the accents, since the formulas are true for any triangle, we have...
Visualització completa - Sobre aquest llibre

## Dublin examination papers

1876
...the relation ra cos A + i cos B -fe cos C B a + b + e 3. In a spherical triangle prove the formula cos c = cos a cos b + sin a sin b cos C, and deduce the corresponding formula by aid of the polar triangle. 4. What do the preceding resslts...
Visualització completa - Sobre aquest llibre

## Plane and Spherical Trigonometry

Henry Nathan Wheeler - 1876 - 208 pągines
.... cos a = cos b cos c + sin b sin c cos A, and similarly cos b = cos c cos a + sin c sin a cos B, ' cos c = cos a cos b + sin a sin b cos C. NOTE. What has been said about the measurement of straight lines in § 2, Plane Trig., will apply equally...
Visualització completa - Sobre aquest llibre

## Catalogue - Harvard University

1876
...angle which differs more from 90° than another angle is in the same quadrant as its opposite side. cos C + cos A cos B = sin A sin B cos c. 2. In the spherical oblique triangle MNO, given m, n, M; obtain, by Napier's and Bowditch's rules,...
Visualització completa - Sobre aquest llibre

## Einleitung in die Krystallberechnung

Karl Klein - 1876 - 393 pągines
...sin b . sin C cos a = cos b . cos c + sin b . sin c cos b = cos a . cos c + sin a . sin c cos A cos B cos c = cos a . cos b + sin a . sin b . cos C ..2), cotg b . sin c = cos G. cos A 4- sin A . cotg B cotg c . sin b — cos b . cos A -t- sin A ....
Visualització completa - Sobre aquest llibre

## Leerboek der rechtlijnige en bolvormige dreihoeksmeting

Rehuel Lobatto - 1877 - 180 pągines
...namelijk cos A = — cos B cos C -f- sin B sin C cos a, cos B = — cos A. cos G + sin A sin G cos b , cos C = — cos A cos B -+- sin A sin B cos c, gevende volgens de herleidingen der vorige paragraaf: sin a = | v . , .—cos S cos (S—A) cos - t*...
Visualització completa - Sobre aquest llibre

## An Elementary Treatise on the Differential Calculus: Containing the Theory ...

Benjamin Williamson - 1877 - 440 pągines
...expression for the difference between the other sides, as far as terms of ihe second order in i. Here cos c = cos a cos b + sin a sin b cos C. Let 2 denote the difference in question ; ie c = a - 2 ; then cos a cos 2 + sin a sin 2 = cos « cos...
Visualització completa - Sobre aquest llibre

## Elemente der Geometrie

Johannes Frischauf - 1877 - 164 pągines
...Dreieck C'AB ist C'A = b" = 2 Л - b, C'B — «" = 2 R - a, Winkel C' = C. Da a" < R, b" <R ist, so ist cos c = cos a" cos b" + sin a" sin b" cos C', cosc = cos(2Д — a)cos(2Л — b) + sin(2B — a)sin(2.ß — b)cosC, woraus wieder cos c = cos a...
Visualització completa - Sobre aquest llibre

## Spherical Trigonometry, for the Use of Colleges and Schools: With Numerous ...

Isaac Todhunter - 1879 - 158 pągines
...free from ambiguity. Or we may determine C without previously determining a and Ъ from the formula cos C = — cos A cos B + sin A sin B cos c. This formula may be adapted to logarithms, thus : cos C = cos B (— cos A + sin A tan B cos c) ; assume...
Visualització completa - Sobre aquest llibre